PENERAPAN SANKSI PIDANA DENDA BAGI PELAKU TINDAK PIDANA RINGAN BERDASARKAN PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2012 (Studi Kasus Putusan Nomor 807/Pid.B/2020/PN.Jkt.Utr) - Natanine Natanine; Hery Firmansyah (Jurnal Hukum Adigama, 2020)
Minor Crimes is a type of crime that is considered to be light and not dangerous. Regulations regarding minor crimes are contained in the Indonesian Criminal Procedure Code (KUHAP) , Indonesian Criminal Code (KUHP) and adjustments were regulated in Supreme Court Regulation Number 2 of 2012. The Supreme Court Regulation was formed because there is a lack of laws regulating minor crimes in the Criminal Code, where the nominal limits and the amount of fines regulated cannot be used in current socio-economic conditions as this time. In addition, based on the 2012 Memorandum of Understanding, the purpose of that Supreme Court Regulation was established to make the fine penalties more effective in the Criminal Code. However, in the Verdict of North Jakarta District Court Number 807/Pid.B/2020/PN.Jkt/ Utr, the minor crimes regulation based on that Supreme Court Regulation were not applied even though the value of the object stolen was under the regulated nominal, and the perpetrators were sentenced to a year in prison instead of sentencing them with fines as per regulated in the Supreme Court Regulation. So the question that arises is, how is the application of fines for perpetrators of minor crimes based on Supreme Court Regulation Number 2 of 2012 in Verdict Number 807 / PID.B / 2020 / PN.Jkt.Utr.?